Challenges in pathological assessment of endoscopic resections. Issue 1 (January 2020) - Moore, Michelle; Lauwers, Gregory Y.; Kumarasinghe, M. Priyanthi
Abstract: Endoscopic resections (ERs) are performed for early (T1) cancers mostly of the esophagus, stomach and colorectum, offering a minimally invasive and tissue-preserving alternative to traditional surgical resection. Proper preparation and handling of these specimens is key to allow accurate histological assessment of parameters which will dictate the curative, or non-curative, nature of the procedure. Many histological features have been identified which correlate with risk of recurrence and/or nodal metastases, thereby dictating the need for further management. These include histological subtype of the lesion, grade, depth of invasion, margin status, tumor size, lymphovascular invasion and tumor budding [at least in the colon]. This review article will discuss the ideal specimen preparation and discuss each of these histological parameters in turn, as they pertain to the esophagus, stomach and colorectum, highlighting potential caveats and pitfalls to be aware of when reporting these specimens.